MULTIPLEKSER BERBASIS PROGRAMMABLE LOGIC DEVICE (PLD) - Muhammad Irmansyah (Teknik Elektro Politeknik Negeri Padang, 2009)
In middle 1990, electronics industry had the evolution of personal Computer, telephone cellular and high speed data communication equipment. To follow this development, electronics companies have designed and produce new product. One of these innovations is Programmable Logic Devices (PLD) technology. It is a technology to change function of IC digital logic using programming. Many of Programmable Logic Device (PLD) can be used to programming logic using single chip of integrated circuit (IC). Programmable Logic Devices (PLD) technology is applied using IC PAL 22V10 to design multiplexer 4 input 1 output and 2 selector.